2016
DOI: 10.1186/s13020-016-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chinese medicine syndromes in persistent insomnia associated with major depressive disorder: a latent tree analysis

Abstract: BackgroundChinese medicine (CM) syndrome (zheng) differentiation is based on the co-occurrence of CM manifestation profiles, such as signs and symptoms, and pulse and tongue features. Insomnia is a symptom that frequently occurs in major depressive disorder despite adequate antidepressant treatment. This study aims to identify co-occurrence patterns in participants with persistent insomnia and major depressive disorder from clinical feature data using latent tree analysis, and to compare the latent variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition to the anti-apoptotic activity, pharmacological activities of CF on the regulation of autophagy can be further explored. Furthermore, many classic Chinese medicinal formulae have been used to treat neurological disorders belonging to liver and kidney deficiency [ 70 – 72 ]. For example, Liuwei Dihuang Wan treats insomnia, Zuogui Wan (左归丸) treats epilepsy and vertigo, Dabu Yinjian (大补阴煎) treats a headache, Zuogui Wan and Dihuang Yinzi (地黄饮子) treats stroke, and Huanshao Dan (还少丹) treats dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the anti-apoptotic activity, pharmacological activities of CF on the regulation of autophagy can be further explored. Furthermore, many classic Chinese medicinal formulae have been used to treat neurological disorders belonging to liver and kidney deficiency [ 70 – 72 ]. For example, Liuwei Dihuang Wan treats insomnia, Zuogui Wan (左归丸) treats epilepsy and vertigo, Dabu Yinjian (大补阴煎) treats a headache, Zuogui Wan and Dihuang Yinzi (地黄饮子) treats stroke, and Huanshao Dan (还少丹) treats dementia.…”
Section: Discussionmentioning
confidence: 99%
“…One key approach to diagnosis is the differentiation of etiopathological pattern which is generally defined by a comprehensive analysis of clinical symptoms and signs collected through inspection, auscultation, olfaction, interrogation, and palpation of the pulses [ 6 ]. Over the past decade, several large-scale studies have revealed 12 different TCM patterns of MDD on the basis of the modern psychiatric diagnostic instruments and analysis tools, such as latent tree model analysis [ 7 – 12 ]. Despite disagreements on some patterns, a consensus on clinical diagnostic criteria for the two most common and opposing patterns, Liver Qi Stagnation (LQS) and Heart and Spleen Deficiency (HSD), which account for approximately 2/3 of depressed patients, have been reached as shown in Table 1 [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 25 Nevertheless, considering the absence of a gold standard test in TCM pattern diagnosis, 45 , 46 , 47 , 48 as well as the poor inter-rater agreement among TCM practitioners in pattern diagnosis, 49 it is doubtful whether diagnoses made by TCM practitioners should serve as the gold standard for criterion validity assessments of TCM diagnostic instruments. Latent class analysis is commonly performed nowadays to explore TCM patterns, with examples from studies conducted among patients with systemic lupus erythematosus, 50 cardiovascular disease, 51 depression, 52 persistent insomnia, 53 and vascular mild cognitive impairment. 48 Since the construct of TCM patterns revealed by latent class analysis may not be a linear combination of relevant TCM signs and symptoms, 35 , 48 , 54 factor analysis may not be suitable for evaluating the structural validity of those diagnostic instruments.…”
Section: Discussionmentioning
confidence: 99%